Systems biology analysis of the WOX5 gene and its functions in the root stem cell niche - E. A. Oshchepkova; N. A. Omelyanchuk; M. S. Savina; T. Pasternak; N. A. Kolchanov; E. V. Zemlyanskaya (Вавиловский журнал генетики и селекции)
WUSCHEL RELATED HOMEOBOX 5 (WOX5) gene encodes the transcription factor, which is one of the key regulators, maintaining structure and functioning of the stem cell niche in plant root tips. Protein WOX5 is expressed in the quiescent center of the root apical meristem, preventing differentiation of columella initials and altogether with SCR, SHR, PLT1 and PLT2 participating in the control of differentiation of other root meristem initials. However, the details of WOX5 functioning are unclear. The WOX5 protein belongs to WUSCHEL related homeobox (WOX) family, the founder of which is the transcription factor WUSCHEL (WUS) providing maintenance of the stem cell niche in the shoot apical meristem. WOX5 and WUS diverged from a common ancestor at the base of angiosperms, which resulted in a specialization of shoot and root stem cell niches. However, the problem of WOX5 structural and functional divergence during angiosperm evolution was poorly addressed. In this review we present a systems biology analysis of the WOX5 gene to reveal specific features of its evolution and functioning. To this end, we performed a phylogenetic analysis on 62 publicly available WOX5 amino acid sequences, generalized published data about WOX5 expression domain in Arabidopsis and other species and its role in development, integrated the results of experiments on identification of primary and secondary targets for this transcription factor. Data on possible mechanisms of direct and indirect regulation of WOX5 expression were discussed. Particularly, we performed the analysis of WOX5 promoter regions from 30 species. Possible direct regulators of the WOX5 gene expression were proposed based on the presence of putative binding sites for the candidate transcription factors in conserved WOX5 promoter regions.